Ploidy level and caffeine content in leaves of Coffea Ploidia e conteúdo de cafeína em folhas de Coffea - Maria Bernadete Silvarolla; Paulo Mazzafera; Marinez Muraro Alves de Lima; Herculano Penna Medina Filho; Luiz Carlos Fazuoli (Scientia Agricola, 1999)
Several species of Coffea and varieties of C. arabica differing in chromosome number had their caffeine content determined in the leaves. For Coffea arabica var. "Angustifolia", var. "Caturra" and var. "Icatu", it was observed caffeine decrease from the haploid (2n = 22) to tetraploid leaves (2n = 44). Caffeine in the tetraploid "Angustifolia" was decreased by 50% when compared to the haploid. Caffeine reduction was also observed in leaves of C. canephora var. "Kouilou" as chromosome number was increased (2n = 22 ® 2n = 44). In this case, caffeine in the leaves of the diploid genotype was close to 4 times higher than in the tetraploid. On the other hand it was observed an increase of the alkaloid when the chromosome number was doubled in the C. canephora var. "Robusta". Variedades e espécies de café (Coffea) que diferem quanto ao número de cromossomos tiveram o conteúdo de cafeína determinado em suas folhas. Para as variedades "Angustifolia", "Caturra" e "Icatu" de Coffea arabica foi observada redução no teor de cafeína de folhas haplóides (2n = 22) em relação a tetraplóides (2n = 44). Cafeína na forma tetraplóide da var. "Angustifolia" foi reduzida em 50% quando comparada com a forma haplóide. Redução de cafeína também foi observada em folhas de C. canephora var. "Kouilou" quando o número de cromossomos aumentou (2n = 22 ® 2n = 44). Neste caso, a cafeína nas folhas do genótipo diplóide foi cerca de quatro vezes maior que no tetraplóide. Por outro lado, foi observado aumento desse alcalóide quando o número de cromossomos foi duplicado em C. canephora var. "Robusta".